2007
DOI: 10.1002/ccd.21221
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde application of the buddy wire technique

Abstract: We report the case of an 85-year-old man who presented with worsening exertional dyspnoea 18 months after coronary artery bypass surgery for critical three vessel coronary artery disease. Coronary angiography revealed an anastomotic stricture between a radial artery graft and the first diagonal branch. Percutaneous coronary intervention utilizing a retrograde application of the "buddy" wire technique was then performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…In a more recent clinical study, Suzuki et al have shown that the average radiation exposure time when treating CTO was 45 ± 24 minutes compared with a reference level of PCI procedure of 16 min [22]. In cases where anterograde approach has failed, a retrograde approach could be used [23, 24]. A wire is introduced directly into the distal vessel beyond the occlusion usually via a large collateral vessel or a bypass graft that connects with the distal vessel and then steered proximally to approach the end of the convex distal fibrous cap.…”
Section: Discussionmentioning
confidence: 99%
“…In a more recent clinical study, Suzuki et al have shown that the average radiation exposure time when treating CTO was 45 ± 24 minutes compared with a reference level of PCI procedure of 16 min [22]. In cases where anterograde approach has failed, a retrograde approach could be used [23, 24]. A wire is introduced directly into the distal vessel beyond the occlusion usually via a large collateral vessel or a bypass graft that connects with the distal vessel and then steered proximally to approach the end of the convex distal fibrous cap.…”
Section: Discussionmentioning
confidence: 99%